Pasang Surut dan Arus Pasang Surut di Area Dermaga Pelabuhan Perikanan Pantai, Muncar, Banyuwangi - Rifqy Firdausyah; Rudi Siap Bintoro; Supriyatno Widagdo (Universitas Hang Tuah, 2023)
Hydro-Oceanographic Parameters are the main factor in supporting the development and periodic maintenance of a port. The research was conducted in November 2021. The data in the study were obtained from observations in the field. The data used in this research is in the form of tidal data and tidal currents. Based on the results of data processing for 1 month in November 2021, the Muncar waters have a mixed tide prevailing semi-diurnal type. The highest tide value during November occurred on November 17 2021 at 22:00 WIB with a water level of 2.6 m and the lowest tide occurred on November 18 2021 at 05:00 WIB with a water level of 0.4 m. Currents move from the Bali Strait towards the Indian Ocean. Just before high tide, the tidal currents move from east to west (entering the anchor pond) with a speed of 0.40 – 0.64 m/s. At low tide, the current moves from West to East (leaving the anchor pond) with a speed of 0.42 – 0.58 m/s.